Analisis Kecukupan Modal dan Loan To Deposit Ratio Terhadap Profitabilitas Perusahaan Perbankan yang Listing di Bursa Efek Indonesia - Faradina Inda Wardhani; Didi Rahmat (Jurnal Ekonomi Integra, 2016)
The purpose of this study was to determine the magnitude of the effect level of Capital Adequacy (Capital Adequacy Ratio - CAR) and liquidity (Loan to Deposit Ratio - LDR) partially and simultaneously on bank profitability. In this research CAR and LDR as the independent variables, and profitability (ROA) as the dependent variable. There are ten of go public banking companies listed in BEI in 2011– 2015 periods that is used as samples, which are selected by purposive sampling. Data were analyzed with multiple regressions. The research, found that the CAR and LDR simultaneously affect the ROA. The two variables are able to explain the variable Profitability amounted to 21.8%, and the balance of 78.2% is explained by other factors. Based on t test, CAR and LDR variables significant effect on the financing of the significance of t count equal to 0,005 and 0,001 (<0.05). Keywords: CAR, LDR, and profitability (ROA)